PENGGUNAAN UBI JALAR SEBAGAI BAHAN SUBSTITUSI KRIM KEJU [THE USE OF SWEET POTATOES AS A CHEESE CREAM SUBSTITUTE] - Kevin Sutarman; Vasco Adato; Jeremy Tan; Liora Pearl Herierna (Universitas Pelita Harapan, 2021)
Ipomoea Batatas or commonly called sweet potato is a kind of tuber that is very familiar to our ears. In addition to its delicious taste and a little sweetness, sweet potatoes are also affordable and easy to find in Indonesia. This is because Indonesia is one of the producers of sweet potatoes. Although the price is affordable and easy to find. However, the use of sweet potatoes every year is decreasing. Even though sweet potatoes offer quite a lot of health benefits such as lowering cholesterol levels, helping to prevent the risk of cardiovascular disease, obesity, and diabetes mellitus. Sweet potatoes are usually consumed by steaming, frying, and processing them into snacks or desserts. During its development, sweet potatoes can also be created as a substitute for other foods such as cheesecake. Cheesecake is a type of dessert that originated in ancient Greece. This dessert is made from main ingredients such as cream cheese and sugar. These two ingredients make cheesecake taste delicious and are popular with people of all ages. However, cream cheese and sugar do not provide nutrients and good uses for the body, where cream cheese can increase cholesterol levels, and sugar can trigger diabetes. In line with the problems found, the team aims to teach how sweet potatoes can be used as a substitute for making desserts in the form of cheesecakes aimed at high school / vocational high school students. It is hoped that high school / vocational high school students will understand more about the use of sweet potatoes and their processing.BAHASA INDONESIA ABSTRACT: Ipomoea Batatas atau yang biasa disebut ubi jalar merupakan sejenis umbi umbian yang sudah sangat akrab di telinga kita. Selain rasanya yang enak dan sedikit manis, ubi jalar juga memiliki harga yang terjangkau dan mudah sekali ditemukan di Indonesia. Hal ini disebabkan karena Indonesia merupakan salah satu produsen penghasil ubi jalar. Meskipun harganya yang terjangkau dan mudah ditemukan. Namun pemanfaatan ubi jalar tiap tahun kian menurun. Padahal ubi jalar menawarkan cukup banyak khasiat bagi kesehatan seperti menurunkan kadar kolesterol, membantu mencegah risiko penyakit kardiovaskular, obesitas, serta diabetes melitus. Ubi jalar biasanya dikonsumsi dengan cara dikukus, digoreng, dan diolah menjadi camilan ataupun hidangan penutup. Pada perkembangannya, ubi jalar juga dapat dikreasikan menjadi bahan pengganti untuk makanan lain seperti cheesecake. Cheesecake merupakan sejenis hidangan penutup yang berasal dari Yunani kuno. Hidangan penutup ini terbuat dari bahan bahan utama seperti krim keju dan gula. Kedua bahan membuat rasa cheesecake menjadi nikmat dan digemari banyak orang dari berbagai umur. Namun krim keju dan gula tidak memberikan nutrisi dan kegunaan yang baik bagi tubuh, dimana krim keju dapat meningkatkan tingkat kolesterol, dan gula dapat memicu diabetes. Sejalan dengan masalah yang ditemukan maka, tim bertujuan untuk memberikan pengajaran bagaimana ubi jalar dapat dimanfaatkan sebagai bahan substitusi untuk membuat hidangan penutup berupa cheesecake yang ditujukan untuk siswa siswi SMA/SMK. Diharapkan siswa siswi SMA/SMK menjadi mengerti lebih lagi mengenai pemanfaatan ubi jalar dan pengolahannya.